2D and 3D urban green space configurations shape airborne microbiome diversity and potential pathogen abundance - Yujia Bai; Mingyu Liao; Peter M. van Bodegom; Laiyi Li; Anyi Hu; Mengran Zhou; Shenghui Cui; Hong Ye (Urban Forestry & Urban Greening, 2026)

Navigating the unknown: Nature-based solutions for coastal climate adaptation under deep uncertainty - Haye H. Geukes; Eva S. Visser; Elena V. Bondarouk; Peter M. van Bodegom; Alexander P.E. van Oudenhoven (Journal of Environmental Management, 2026)

Low mycovirus presence in soil saprotrophic fungi in Dutch sandy soils - Ruiqi Wang; Hazal Kandemir; Jing Zhang; T. Martijn Bezemer; Peter M. van Bodegom; S. Emilia Hannula (European Journal of Soil Biology, 2025)

Hybrid modelling of leaf traits: Integrating neural networks with radiative transfer theory - Peng Sun; Peter M. van Bodegom; Joris Timmermans; Shuwen Liu; Jin Wu; Marco D. Visser (Remote Sensing of Environment, 2025)

CO 2 Rise Directly Impairs Crop Nutritional Quality - Sterre F. ter Haar; Peter M. van Bodegom; Laura Scherer (Global Change Biology, 2025)
Rising CO 2 levels indirectly affect food availability (e.g., through climate shifts, biological consequences, and shifting socioeconomic systems). Less known is the direct effect of CO 2 on nutrient availability by changing the plant stoichiometry. We help fill this gap, presenting a new methodology and creating the largest meta‐analysis on edible plant parts to date, including the most data (5324 entries covering 29,524 observation pairs), crops (43), and (anti)nutrients (32). The results show a pervasive elemental shift across a wide range of species as CO 2 rises. Elements respond differentially, with zinc decreasing the most. Plants with not only a C3 but also a C4 photosynthetic pathway respond. Impacts vary by species and tissue type. This stoichiometric shift can lead to (worsening) malnutrition even in previously sufficient populations. Nutrient security is under threat even if food security remains adequate; food will become more caloric and less nutritious.

Fish functional diversity responses to total phosphorus in the rivers of the Baltic Sea catchment area - Māra Deksne; Peter M. van Bodegom; Laura Scherer (Environmental Pollution, 2025)

Solution to what? Global assessment of nature-based solutions, urban challenges, and outcomes - Meng Li; Roy P. Remme; Peter M. van Bodegom; Alexander P.E. van Oudenhoven (Landscape and Urban Planning, 2025)

Networks in Aquatic Communities Collapse Upon Neonicotinoid‐Induced Stress - S. Henrik Barmentlo; Maarten Schrama; Ellen Cieraad; Geert R. de Snoo; C. J. M. Musters; Peter M. van Bodegom; Martina G. Vijver (Ecology Letters, 2025)
Freshwater ecosystems worldwide are under pressure from neonicotinoid insecticides. While it is recognised that communities of species are responsible for ecosystem functioning, it remains unknown if neonicotinoid‐induced community transformations negatively affect ecosystem functioning. Therefore, we employed an experimental approach with 36 naturally established freshwater ecosystems exposed to increasing field‐realistic concentrations of the neonicotinoid thiacloprid. Upon exposure, we found severe degradation of ecosystem functioning in the form of loss of organic matter consumption and dramatic shifts in primary productivity. This functional decline coincides with strongly eroded species co‐occurrence networks to the point that these are indistinguishable from randomised assemblages of species. Together, these findings show how current environmental concentrations of a neonicotinoid can strongly disrupt freshwater ecosystem functioning via degradation of the invertebrate food web. Since this dramatic ecosystem degradation occurs below nearly all identified ecotoxicological risks, we call here for the reconsideration of the use of these insecticides.

When can we detect lianas from space? Toward a mechanistic understanding of liana‐infested forest optics - Marco D. Visser; Matteo Detto; Félicien Meunier; Jin Wu; Jane R. Foster; David C. Marvin; Peter M. van Bodegom; Boris Bongalov; Matheus Henrique Nunes; David Coomes; Hans Verbeeck; J. Antonio Guzmán Q; et al. (Ecology, 2025)
Lianas, woody vines acting as structural parasites of trees, have profound effects on the composition and structure of tropical forests, impacting tree growth, mortality, and forest succession. Remote sensing could offer a powerful tool for quantifying the scale of liana infestation, provided the availability of robust detection methods. We analyze the consistency and global geographic specificity of spectral signals—reflectance across wavelengths—from liana‐infested tree crowns and forest stands, examining the underlying mechanisms of these signals. We compiled a uniquely comprehensive database, including leaf reflectance spectra from 5424 leaves, fine‐scale airborne reflectance data from 999 liana‐infested canopies, and coarse‐scale satellite reflectance data covering 775 ha of liana‐infested forest stands. To unravel the mechanisms of the liana spectral signal, we applied mechanistic radiative transfer models across scales, establishing a synthesis of the relative importance of different mechanisms, which we corroborate with field data on liana leaf chemistry and canopy structure. We find a consistent liana spectral signal at canopy and stand scales across globally distributed sites. This signature mainly arises at the canopy level due to direct effects of more horizontal leaf angles, resulting in a larger projected leaf area, and indirect effects from increased light scattering in the near and short‐wave infrared regions, linked to lianas' less costly leaf construction compared with trees on average. The existence of a consistent global spectral signal for lianas suggests that large‐scale quantification of liana infestation is feasible. However, because the traits responsible for the liana canopy‐reflectance signal are not exclusive to lianas, accurate large‐scale detection requires rigorously validated remote sensing methods. Our models highlight challenges in automated detection, such as potential misidentification due to leaf phenology, tree life history, topography, and climate, especially where the scale of liana infestation is less than a single remote sensing pixel. The observed cross‐site patterns also prompt ecological questions about lianas' adaptive similarities in optical traits across environments, indicating possible convergent evolution due to shared constraints on leaf biochemical and structural traits.

Convergent Strategies for Leaf Traits in Tree Species From Divergent Habitats - Hanfeng Xu; Yu Song; Yun‐Hong Tan; Dashan He; Yuchuan Yang; Peter M. van Bodegom; Josep Peñuelas; Yingji Pan; Lei Chen (Global Change Biology, 2025)
Plant trait expressions and their trade‐offs reflect the responses and long‐term ecological adaptation to environmental gradients. However, how such expressions and trade‐offs help plants to acclimate to a new environment remains poorly understood, which is a fundamental preset for plants' survival under a global change scenario. By comparing the trait–trait relationships of 4403 tree species from different climatic regions and the variation in trait trade‐offs of 746 tree species that have been transplanted to a tropical botanical garden for several decades, our results reveal convergent but consistent alteration in trait–trait relationships of trees transplanted from different climatic regions to a common environment. The convergent trends enhance the capability of tree species in buffering the impacts of climate change through allocating more resources to growth and tolerance. We propose that altered trait–trait relationships may be the key mechanisms that underlie the long‐term ecological stability and resilience of tree species.

Land‐Use Impacts on Plant Functional Diversity Throughout Europe - Francesca Rosa; Peter M. van Bodegom; Stefanie Hellweg; Stephan Pfister; Idoia Biurrun; Steffen Boch; Milan Chytrý; Renata Ćušterevska; Michele Dalle Fratte; Gabriella Damasceno; Emmanuel Garbolino; Jonathan Lenoir; et al. (Global Ecology and Biogeography, 2025)
Aim Global biodiversity loss resulting from anthropogenic land‐use activities is a pressing concern, requiring precise assessments of impacts at large spatial extents. Existing models mainly focus on species richness and abundance, lacking insights into ecological mechanisms and species' roles in ecosystem functioning. To bridge this gap, we conducted an extensive analysis of the impact of human land use on vascular plant functional diversity across diverse land‐use classes and bioregions in Europe, comparing it to traditional metrics. Location Europe. Time Period 1992–2019. Major Taxa Studied Vascular plants. Methods Integrating extensive databases of vegetation plots with spatial data on land use and land cover, we paired plots from areas actively used and modified by humans with plots from natural habitats under similar environmental conditions. Using species occurrences and traits, in each plot we computed three complementary functional diversity metrics (functional richness, evenness and divergence), species richness and abundance. We assessed the impact of land use by comparing the metrics in the paired plots. Results Our findings revealed that, compared to natural habitats, anthropogenic land use exhibits lower functional richness and divergence but higher functional evenness across most land‐use classes and bioregions. The response of functional richness was more marked than the other two metrics and especially pronounced in croplands and urban areas and in northern bioregions. Functional richness exhibited a pattern that did not fully overlap with the trend in species richness, providing useful complementary information. Main Conclusions We provide a large‐scale precise assessment of anthropogenic land‐use impacts on functional diversity across Europe. Our findings indicate that: (i) human disturbance significantly alters plant functional diversity compared to natural habitats; (ii) this alteration goes in the direction of functional homogenisation within sites; (iii) functional diversity metrics complement traditional metrics by offering deeper insights into the ecological mechanisms in response to anthropogenic land use.

Land use intensity differently affects soil microbial functional communities in arable fields - Chenguang Gao; S. Emilia Hannula; Peter M. van Bodegom; T. Martijn Bezemer; Franciska T. de Vries; Jan Hassink; Michiel H. in ’t Zandt; Gabriel Y.K. Moinet (Applied Soil Ecology, 2024)

Trade-offs in soil microbial functions and soil health in agroecosystems - Chenguang Gao; Thiemo Martijn Bezemer; Franciska T. de Vries; Peter M. van Bodegom (Trends in Ecology & Evolution, 2024)

Training-free thick cloud removal for Sentinel-2 imagery using value propagation interpolation - Laurens Arp; Holger Hoos; Peter van Bodegom; Alistair Francis; James Wheeler; Dean van Laar; Mitra Baratchi (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Intercomparison of global foliar trait maps reveals fundamental differences and limitations of upscaling approaches - Benjamin Dechant; Jens Kattge; Ryan Pavlick; Fabian D. Schneider; Francesco M. Sabatini; Álvaro Moreno-Martínez; Ethan E. Butler; Peter M. van Bodegom; Helena Vallicrosa; Teja Kattenborn; Coline C.F. Boonman; Nima Madani; et al. (Remote Sensing of Environment, 2024)

Global increase of lianas in tropical forests - Manuela A. Rueda‐Trujillo; Michiel P. Veldhuis; Peter M. van Bodegom; Hannes P. T. de Deurwaerder; Marco Visser (Global Change Biology, 2024)
Lianas profoundly affect tropical forests dynamics, reducing productivity and carbon storage, which underscores the importance of monitoring change in their abundance in projecting the future of the global terrestrial carbon store. While increasing liana populations are documented within the Neotropics, the global consistency of these patterns is questioned, and remains to be determined. To evaluate pantropical trends in liana abundance comprehensively and quantitatively, we conducted a systematic literature review and meta‐analysis. This approach allowed us to synthesize data from published longitudinal studies examining liana trends across the tropics. We calculated standardized effect sizes and standard errors, and applied a Bayesian hierarchical meta‐analytic model to adjust for publication bias. Our analysis reveals an overall pan‐tropical increase in lianas abundance, occurring at an average rate of 1.7 ± 0.7 SE% per year (~10% to 24% per decade). This upward trend, confirmed to be robust against publication bias, extends beyond Neotropical regions, indicating a widespread phenomenon. Although a global trend of increasing liana abundance is evident, significant local variation exist, attributable to differences in life cycle stages, abundance metrics, forest successional stages, and biogeographical realms. Notably, increases in stem density of saplings and biomass of canopy lianas, especially in old‐growth forests, point to global climatic drivers and heightened turnover rates in tropical forests as factors promoting sustained liana growth in the canopy and clonal colonization in the understory. These trends suggest that the rise in liana abundance may not only persist but could also intensify under climate change. Considering both previous and current research on lianas, our findings confirm growing concerns about lianas' expanding impact on pan‐tropical carbon storage, highlighting their significant potential effect on global carbon dynamics.

Fungal communities are passengers in community development of dune ecosystems, while bacteria are not - Chenguang Gao; T. Martijn Bezemer; Peter M. van Bodegom; Petr Baldrian; Petr Kohout; Riccardo Mancinelli; Harrie van der Hagen; Nadejda A. Soudzilovskaia (Ecology, 2024)
An increasing number of studies of above‐belowground interactions provide a fundamental basis for our understanding of the coexistence between plant and soil communities. However, we lack empirical evidence to understand the directionality of drivers of plant and soil communities under natural conditions: ‘Are soil microorganisms driving plant community functioning or do they adapt to the plant community?’ In a field experiment in an early successional dune ecosystem, we manipulated soil communities by adding living (i.e., natural microbial communities) and sterile soil inocula, originating from natural ecosystems, and examined the annual responses of soil and plant communities. The experimental manipulations had a persistent effect on the soil microbial community with divergent impacts for living and sterile soil inocula. The plant community was also affected by soil inoculation, but there was no difference between the impacts of living and sterile inocula. We also observed an increasing convergence of plant and soil microbial composition over time. Our results show that alterations in soil abiotic and biotic conditions have long‐term effects on the composition of both plant and soil microbial communities. Importantly, our study provides direct evidence that soil microorganisms are not “drivers” of plant community dynamics. We found that soil fungi and bacteria manifest different community assemblies in response to treatments. Soil fungi act as “passengers,” that is, soil microorganisms reflect plant community dynamics but do not alter it, whereas soil bacteria are neither “drivers” nor “passengers” of plant community dynamics in early successional ecosystems. These results are critical for understanding the community assembly of plant and soil microbial communities under natural conditions and are directly relevant for ecosystem management and restoration.

Assessing nutrient fate from terrestrial to freshwater systems using a semi-distributed model for the Fuxian Lake Basin, China - Jinhui Zhou; José M. Mogollón; Peter M. van Bodegom (Science of The Total Environment, 2024)

Creating the Dutch One Health Shared Socio-economic Pathways (SSPs) - Martha Dellar; Gertjan Geerling; Kasper Kok; Peter van Bodegom; Maarten Schrama; Eline Boelee (Regional Environmental Change, 2024)
The world is changing, in terms of both climate and socio-economics. These changes have the potential to have a profound impact on the health of humans, animals and the environment, often grouped together as ‘One Health’. Humans, animals and the environment are closely interlinked and to determine realistic future vulnerabilities we must consider everything together. We need comprehensive scenarios which cover a broad range of variables affecting One Health. We developed a methodology to create national-level One Health scenarios based on the global Shared Socio-economic Pathways (SSPs), which we applied to the Netherlands. We identified variables which should be included in such scenarios and gathered input from existing scenarios, stakeholder consultation and current plans and commitments. This information was combined to create detailed descriptions, which were used to assess the main health risks under each scenario. All the scenarios face similar challenges, for example an aging population, introductions of infectious diseases and rising sea-levels and extreme weather events; however, in some scenarios, they deal with these challenges much better than in others. The healthiest outcome was achieved when a policy of low greenhouse gas emissions was combined with a well-functioning society which looks after both its citizens and the environment. These scenarios can be used to analyse specific health risks and to consider options for mitigation and preparedness. Because they are national-level scenarios, they allow the local context, policies and customs to be accounted for and should be a valuable tool for protecting One Health in the future.

Global regionalized characterization factors for phosphorus and nitrogen impacts on freshwater fish biodiversity - Jinhui Zhou; José M. Mogollón; Peter M. van Bodegom; Arthur H.W. Beusen; Laura Scherer (Science of The Total Environment, 2024)

Setting the stage for decision-making on nature-based solutions for coastal climate adaptation - Haye H. Geukes; Peter M. van Bodegom; Alexander P.E. van Oudenhoven (Ocean & Coastal Management, 2024)

Response letter to correspondence letter: “Tropical deforestation: elections vs. bad governance” - Joeri Morpurgo; W. Daniel Kissling; Peter Tyrrell; Pablo J. Negret; Peter M. van Bodegom; James R. Allan (Biological Conservation, 2023)

Climate change threats to the global functional diversity of freshwater fish - Laura Scherer; Hidde A. Boom; Valerio Barbarossa; Peter M. van Bodegom (Global Change Biology, 2023)
Climate change impacts on freshwater ecosystems and freshwater biodiversity show strong spatial variability, highlighting the importance of a global perspective. While previous studies on biodiversity mostly focused on species richness, functional diversity, which is a better predictor of ecosystem functioning, has received much less attention. This study aims to comprehensively assess climate change threats to the functional diversity of freshwater fish across the world, considering three complementary metrics—functional richness, evenness and divergence. We built on existing spatially explicit projections of geographical ranges for 11,425 riverine fish species as affected by changes in streamflow and water temperature extremes at four warming levels (1.5°C, 2.0°C, 3.2°C and 4.5°C). To estimate functional diversity, we considered the following four continuous, morphological and physiological traits: relative head length, relative body depth, trophic level and relative growth rate. Together, these traits cover five ecological functions. We treated missing trait values in two different ways: we either removed species with missing trait values or imputed them. Depending on the warming level, 6%–25% of the locations globally face a complete loss of functional diversity when assuming no dispersal (6%–17% when assuming maximal dispersal), with hotspots in the Amazon and Paraná River basins. The three facets of functional diversity do not always follow the same pattern. Sometimes, functional richness is not yet affected despite species loss, while functional evenness and divergence are already reducing. Other times, functional richness reduces, while functional evenness and/or divergence increase instead. The contrasting patterns of the three facets of functional diversity show their complementarity among each other and their added value compared to species richness. With increasing climate change, impacts on freshwater communities accelerate, making early mitigation critically important.

Beta diversity of urban spontaneous plants and its drivers in 9 major cities of Yunnan province, China - Zhiwen Gao; Yingji Pan; Peter M. Van Bodegom; Ellen Cieraad; Dingliang Xing; Yanyi Yang; Tiyuan Xia; Xinyi Luo; Kun Song; Liangjun Da; Dan Malkinson (Landscape and Urban Planning, 2023)

CUGIC: The Consolidated Urban Green Infrastructure Classification for assessing ecosystem services and biodiversity - Joeri Morpurgo; Roy P. Remme; Peter M. Van Bodegom (Landscape and Urban Planning, 2023)

Ecosystems threatened by intensified drought with divergent vulnerability - Qi Chen; Joris Timmermans; Wen Wen; Peter M. van Bodegom (Remote Sensing of Environment, 2023)

Soil Biota Adversely Affect the Resistance and Recovery of Plant Communities Subjected to Drought - Chenguang Gao; Peter M. van Bodegom; T. Martijn Bezemer; Michiel P. Veldhuis; Riccardo Mancinelli; Nadejda A. Soudzilovskaia (Ecosystems, 2023)
Climate change predictions indicate that summer droughts will become more severe and frequent. Yet, the impact of soil communities on the response of plant communities to drought remains unclear. Here, we report the results of a novel field experiment, in which we manipulated soil communities by adding soil inocula originating from different successional stages of coastal dune ecosystems to a plant community established from seeds on bare dune sand. We tested if and how the added soil biota from later-successional ecosystems influenced the sensitivity (resistance and recovery) of plant communities to drought. In contrast to our expectations, soil biota from later-successional soil inocula did not improve the resistance and recovery of plant communities subjected to drought. Instead, inoculation with soil biota from later successional stages reduced the post-drought recovery of plant communities, suggesting that competition for limited nutrients between plant community and soil biota may exacerbate the post-drought recovery of plant communities. Moreover, soil pathogens present in later-successional soil inocula may have impeded plant growth after drought. Soil inocula had differential impacts on the drought sensitivity of specific plant functional groups and individual species. However, the sensitivity of individual species and functional groups to drought was idiosyncratic and did not explain the overall composition of the plant community. Based on the field experimental evidence, our results highlight the adverse role soil biota can play on plant community responses to environmental stresses. These outcomes indicate that impacts of soil biota on the stability of plant communities subjected to drought are highly context-dependent and suggest that in some cases the soil biota activity can even destabilize plant community biomass responses to drought.

The role of elections as drivers of tropical deforestation - Joeri Morpurgo; W. Daniel Kissling; Peter Tyrrell; Pablo J. Negret; Peter M. van Bodegom; James R. Allan (Biological Conservation, 2023)

Community adaptation to temperature explains abrupt soil bacterial community shift along a geothermal gradient on Iceland - James T. Weedon; Erland Bååth; Ruud Rijkers; Stephanie Reischke; Bjarni D. Sigurdsson; Edda Oddsdottir; Jurgen van Hal; Rien Aerts; Ivan A. Janssens; Peter M. van Bodegom (Soil Biology and Biochemistry, 2023)

Characterization factors for ocean acidification impacts on marine biodiversity - Laura Scherer; İrem Gürdal; Peter M. van Bodegom (Journal of Industrial Ecology, 2022)
Rising greenhouse gas emissions do not only accelerate climate change but also make the ocean more acidic. This applies above all to carbon dioxide (CO 2 ). Lower ocean pH levels threaten marine ecosystems and especially strongly calcifying species. Impacts on marine ecosystem quality are currently underrepresented in life cycle assessments (LCAs). Here, we developed characterization factors for the life cycle impact assessment of ocean acidification. Our main contribution was developing new species sensitivity distributions (SSDs), from which we derived effect factors for different impact perspectives: Marginal, linear, and average changes for both the past and four future emission scenarios (RCP2.6, RCP4.5, RCP6.0, and RCP8.5). Based on a dataset that covered five taxa (corals, crustaceans, echinoderms, fishes, molluscs) and three climate zones, we showed significantly higher sensitivities for strongly calcifying than slightly calcifying taxa and in polar regions compared to tropical and temperate regions. Experimental duration, leading to acute, subchronic, or chronic toxicological endpoints, did not significantly affect the species sensitivities. With ocean acidification impacts still accelerating, the future‐oriented average effects are higher than the marginal or past‐oriented average effects. While our characterization factors are ready for use in LCA, we also point to opportunities for improvement in future developments.

Regionalized nitrogen fate in freshwater systems on a global scale - Jinhui Zhou; Laura Scherer; Peter M. van Bodegom; Arthur Beusen; José M. Mogollón (Journal of Industrial Ecology, 2022)

Assessing the use of land system archetypes to increase regional variability representation in country-specific characterization factors: a soil erosion case study - Elizabeth M. Alejandre; Jeroen B. Guinée; Peter M. van Bodegom (The International Journal of Life Cycle Assessment, 2022)
Purpose The characterization of land use impacts in life cycle assessment (LCA) requires a constant compromise between highly specific impacts models and coarse geographical scales available in life cycle inventory, where most information is provided at country level as the highest degree of geographical specificity. The derivation of country-specific characterization factors is usually done estimating impacts with the use of land cover and potential natural vegetation maps, assuming the most predominant biome per country as representative. This study explores the use of land system archetypes to derive country-specific characterization factors for land use-related soil erosion impacts that can better represent intra-national variations, while accounting for several biogeographical and socioeconomic differences. Methods Land use-specific characterization factors were derived as the potentially enhanced soil erosion rate, using the soil erosion rates of each archetype as a reference state, and correction factors to reflect the relative increase or decrease in soil erosion rates associated with each of the eight land use types assessed: forest, permanent crops, grassland, farmland, fallow ground, moorland, urban/industrial, and mining/landfill. Country-specific characterization factors for land use erosion impacts of occupation (in ton/(m 2 ·year)) were calculated by taking into account the land system archetypes present in each country, the land use-specific characterization factors, and the likelihood of each land use type occurring across archetypes (based on rule of thumb expert estimates). The country-specific characterization factors were produced specifically for occupation impacts for each of the eight land use types, and covering 263 countries and territories/dependencies. Results and discussion The resulting 2,104 country-specific characterization factors displayed in average a considerably greater variation in comparison with characterization factors produced when only the most predominant archetype per country is assumed as representative per country. The results indicate that world generic values might underestimate up to 10 times the degree of impacts associated with land use types such as permanent crops, fallow ground, mining, and landfill. The use of land system archetypes presents a viable approach to derive country-specific characterization factors while taking into account key intra-national variations, as well as biogeographical and socioeconomic factors.

Dugong foraging behavior on tropical intertidal seagrass meadows: the influence of climatic drivers and anthropogenic disturbance - Anugrah A. Budiarsa; H. H. De Iongh; Wawan Kustiawan; Peter M. van Bodegom (Hydrobiologia, 2021)
Foraging strategies of dugongs in tropical areas are not yet well understood, and that is particularly true for grazing of fast-growing pioneer seagrass meadows in the intertidal zones. In this study, we investigated the driving factors affecting the number of grazing tracks in intertidal seagrass meadows caused by small herds of dugongs in Balikpapan Bay, Indonesia. We investigated seven intertidal seagrass meadows for which the dynamics of seagrass biomass, the ratio aboveground to belowground biomass, and the number of grazing tracks were recorded and measured based on monthly intervals over a year. Seagrass features showed a significant relationship with wind speed, precipitation, desiccation time, the distance of the grazing sward to a residential area, and fishing activity based on multiple (generalized) linear models. While the intertidal seagrass meadows consisted of 5 species in total, only Halodule pinifolia patches were grazed. Dugong feeding tracks were found in four of the seven sites. The strong variation in the number of tracks throughout the year was significantly affected by seagrass biomass of seagrass, location and wind speed. Our results show how the interplay of site conditions related to both shelter (wind speed) and food availability (seagrass biomass) determines its suitability for dugongs.

Global root traits (GRooT) database - Nathaly R. Guerrero‐Ramírez; Liesje Mommer; Grégoire T. Freschet; Colleen M. Iversen; M. Luke McCormack; Jens Kattge; Hendrik Poorter; Fons van der Plas; Joana Bergmann; Thom W. Kuyper; Larry M. York; Helge Bruelheide; et al. (Global Ecology and Biogeography, 2021)
Motivation Trait data are fundamental to the quantitative description of plant form and function. Although root traits capture key dimensions related to plant responses to changing environmental conditions and effects on ecosystem processes, they have rarely been included in large‐scale comparative studies and global models. For instance, root traits remain absent from nearly all studies that define the global spectrum of plant form and function. Thus, to overcome conceptual and methodological roadblocks preventing a widespread integration of root trait data into large‐scale analyses we created the Global Root Trait (GRooT) Database. GRooT provides ready‐to‐use data by combining the expertise of root ecologists with data mobilization and curation. Specifically, we (a) determined a set of core root traits relevant to the description of plant form and function based on an assessment by experts, (b) maximized species coverage through data standardization within and among traits, and (c) implemented data quality checks. Main types of variables contained GRooT contains 114,222 trait records on 38 continuous root traits. Spatial location and grain Global coverage with data from arid, continental, polar, temperate and tropical biomes. Data on root traits were derived from experimental studies and field studies. Time period and grain Data were recorded between 1911 and 2019. Major taxa and level of measurement GRooT includes root trait data for which taxonomic information is available. Trait records vary in their taxonomic resolution, with subspecies or varieties being the highest and genera the lowest taxonomic resolution available. It contains information for 184 subspecies or varieties, 6,214 species, 1,967 genera and 254 families. Owing to variation in data sources, trait records in the database include both individual observations and mean values. Software format GRooT includes two csv files. A GitHub repository contains the csv files and a script in R to query the database.

Simulating functional diversity of European natural forests along climatic gradients - Kirsten Thonicke; Maik Billing; Werner von Bloh; Boris Sakschewski; Ülo Niinemets; Josep Peñuelas; J. Hans C. Cornelissen; Yusuke Onoda; Peter van Bodegom; Michael E. Schaepman; Fabian D. Schneider; Ariane Walz (Journal of Biogeography, 2020)
Aim We analyse how functional diversity (FD) varies across European natural forests to understand the effects of environmental and competitive filtering on plant trait distribution. Location Forest ecosystems in Europe from 11°W to 36°E and 29.5°N to 62°N. Taxon Pinaceae, Fagaceae and Betulaceae, Oleaceae, Tiliaceae, Aceraceae, Leguminosae (unspecific). Methods We adopted the existing Dynamic Global Vegetation Model Lund‐Potsdam‐Jena managed Land of flexible individual traits (LPJmL‐FIT) for Europe by eliminating both bioclimatic limits of plant functional types (PFTs) and replacing prescribed values of functional traits for PFTs with emergent values under influence of environmental filtering and competition. We quantified functional richness (FR), functional divergence (FDv) and functional evenness (FE) in representative selected sites and at Pan‐European scale resulting from simulated functional and structural trait combinations of individual trees. While FR quantifies the amount of occupied trait space, FDv and FE describe the distribution and abundance of trait combinations, respectively, in a multidimensional trait space. Results Lund‐Potsdam‐Jena managed Land of flexible individual traits reproduces spatial PFTs and local trait distributions and agrees well with observed productivity, biomass and tree height of European natural forests. The observed site‐specific trait distributions and spatial gradients of traits of the leaf‐ and stem‐resource economics spectra coincide with environmental filtering and the competition for light and water in environments with strong abiotic stress. Where deciduous and needle‐leaved trees co‐occur, for example, in boreal and mountainous forests, the potential niche space is wide (high FR), and extreme ends in the niche space are occupied (high FDv). We find high FDv in Mediterranean forests where drought increasingly limits tree growth, thus niche differentiation becomes more important. FDv decreases in temperate forests where a cold climate increasingly limits growth efficiency of broad‐leaved summer green trees, thus reducing the importance of competitive exclusion. Highest FE was simulated in wet Atlantic and southern Europe which indicated relatively even niche occupation and thus high resource‐use efficiency. Main Conclusions We find FD resulting from both environmental and competitive filtering. Pan‐European FR, FDv and FE demonstrate the influence of climate gradients and intra‐ and inter‐PFT competition. The indices underline a generally high FD of natural forests in Europe. Co‐existence of functionally diverse trees across PFTs emerges from alternative (life‐history) strategies, disturbance and tree demography.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Evaluating the potential contribution of urban ecosystem service to climate change mitigation - Vahid Amini Parsa; Esmail Salehi; Ahmad Reza Yavari; Peter M. van Bodegom (Urban Ecosystems, 2019)

Global distribution patterns of mycoheterotrophy - Sofia I. F. Gomes; Peter M. van Bodegom; Vincent S. F. T. Merckx; Nadejda A. Soudzilovskaia (Global Ecology and Biogeography, 2019)
Aim Mycoheterotrophy is a mode of life where plants cheat the mycorrhizal symbiosis, receiving carbon via their fungal partners. Despite being widespread, mycoheterotrophic plants are locally rare, hampering the understanding of their global environmental drivers. Here, we explore global environmental preferences of mycoheterotrophy, and investigate environmental drivers of differential habitat preferences of mycoheterotrophic plants associated with arbuscular (AM) and ectomycorrhizal (EM) fungi. Location Global. Time period Current. Major taxa studied Mycoheterotrophic flowering plants. Methods We compiled the largest global dataset of epiparasitic mycoheterotrophic plant species occurrences and examined which environmental factors, including soil type, climate, vegetation type and distribution patterns of mycorrhizal autotrophic plants, relate to occurrence patterns of mycoheterotrophic plant species associated with AM and EM fungi. Results Mycoheterotrophic plant species avoid cold and highly seasonal climates and show a strong preference for forests. AM‐associated mycoheterotrophs are predominantly found in broadleaved tropical evergreen forests whereas EM‐associated mycoheterotrophs occur in temperate regions, mostly in broadleaved deciduous and evergreen needleleaved forests. The abundance of AM and EM autotrophic plants was a weaker predictor for mycoheterotrophs occurrences than forest type. Temperature and precipitation variables – but not edaphic factors – were the best predictors explaining the distribution patterns of mycoheterotrophs after accounting for the effects of forest type. For individual lineages, major differences in environmental preferences (often related to edaphic factors) occurred that were significantly associated with plant evolutionary relationships, indicating that these cheater plants have limited adaptive capabilities. Main conclusions The strong global geographical segregation of AM and EM mycoheterotrophs does not reflect the abundance of their potential autotrophic hosts, but seems to be driven by differential climate and habitat preferences. Our results highlight the non‐trivial nature of mycorrhizal interactions, and indicate that identity of the partners is not enough to understand the underlying mechanisms promoting plant–fungal interactions in mycoheterotrophic plants.

Evaluation and selection of functional diversity metrics with recommendations for their use in life cycle assessments - Danish Ali Ahmed; Peter M. van Bodegom; Arnold Tukker (The International Journal of Life Cycle Assessment, 2019)

Spatial scale dependence of factors driving climate regulation services in the Americas - Hector M. Serna‐Chavez; W. Daniel Kissling; Lourens E. Veen; Nathan G. Swenson; Peter M. van Bodegom (Global Ecology and Biogeography, 2018)
Aim A key hypothesis in macroecology is that the relative importance of factors driving ecological phenomena changes with spatial scale. However, studies on ecosystem services usually ignore this. Here, we test how the importance of factors related to climate regulation services varies with spatial extent (i.e., area of assessment) and how covariation among factors affects scale dependencies. Location The Americas. Time period Present. Major taxa studied Plants. Methods We combined a multi‐model inference framework with variance partitioning to quantify the importance of factors that could potentially influence climate regulation services (i.e., albedo, evapotranspiration and primary productivity). We quantified abiotic (climate, soil, heterogeneity in soils/topography), biotic (open vegetation, forest area and biomass, plant functional traits) and anthropogenic (forest fragmentation, managed vegetation, non‐vegetated surfaces) conditions and tested their importance in relation to climate regulation services at spatial extents ranging from 9 × 10 3 to 1 × 10 6 km 2 . Results We found that the importance of abiotic factors in relation to climate regulation services increases with spatial extent. However, we found no evidence for a change from primarily biotically to abiotically driven climate regulation services with increasing spatial extent. All spatial extent dependencies were heavily influenced by covariation between abiotic, biotic and anthropogenic factors. After accounting for covariation, we found a primacy of abiotic factors as drivers of climate regulation services across spatial extents. Biotic and anthropogenic factors were less important than abiotic factors, and their independent effects were conserved across spatial extents. Main conclusions Our results show that the relative importance of abiotic factors related to climate regulation services depends on spatial extent. Biotic and anthropogenic factors are less important for climate regulation services than abiotic factors, and this hierarchy is scale invariant. Our findings suggest that spatial extent dependence needs to be quantified and assessed in climate‐change mitigation projects that focus on ecosystem services.

Spatial patterns and climate relationships of major plant traits in the New World differ between woody and herbaceous species - Irena Šímová; Cyrille Violle; Jens‐Christian Svenning; Jens Kattge; Kristine Engemann; Brody Sandel; Robert K. Peet; Susan K. Wiser; Benjamin Blonder; Brian J. McGill; Brad Boyle; Naia Morueta‐Holme; et al. (Journal of Biogeography, 2018)
Aim Despite several recent efforts to map plant traits and to identify their climatic drivers, there are still major gaps. Global trait patterns for major functional groups, in particular, the differences between woody and herbaceous plants, have yet to be identified. Here, we take advantage of big data efforts to compile plant species occurrence and trait data to analyse the spatial patterns of assemblage means and variances of key plant traits. We tested whether these patterns and their climatic drivers are similar for woody and herbaceous plants. Location New World (North and South America). Methods Using the largest currently available database of plant occurrences, we provide maps of 200 × 200 km grid‐cell trait means and variances for both woody and herbaceous species and identify environmental drivers related to these patterns. We focus on six plant traits: maximum plant height, specific leaf area, seed mass, wood density, leaf nitrogen concentration and leaf phosphorus concentration. Results For woody assemblages, we found a strong climate signal for both means and variances of most of the studied traits, consistent with strong environmental filtering. In contrast, for herbaceous assemblages, spatial patterns of trait means and variances were more variable, the climate signal on trait means was often different and weaker. Main conclusion Trait variations for woody versus herbaceous assemblages appear to reflect alternative strategies and differing environmental constraints. Given that most large‐scale trait studies are based on woody species, the strikingly different biogeographic patterns of herbaceous traits suggest that a more synthetic framework is needed that addresses how suites of traits within and across broad functional groups respond to climate.

Plant community structure and nitrogen inputs modulate the climate signal on leaf traits - Benjamin Borgy; Cyrille Violle; Philippe Choler; Pierre Denelle; François Munoz; Jens Kattge; Sandra Lavorel; Jessy Loranger; Bernard Amiaud; Michael Bahn; Peter M. van Bodegom; Henry Brisse; et al. (Global Ecology and Biogeography, 2017)
Aim Leaf traits strongly impact biogeochemical cycles in terrestrial ecosystems. Understanding leaf trait variation along environmental gradients is thus essential to improve the representation of vegetation in Earth system models. Our aims were to quantify relationships between leaf traits and climate in permanent grasslands at a biogeographical scale and to test whether these relationships were sensitive to (a) the level of nitrogen inputs and (b) the inclusion of information pertaining to plant community organization. Location Permanent grasslands throughout France. Methods We combined existing datasets on climate, soil, nitrogen inputs (fertilization and deposition), species composition and four traits, namely specific leaf area, leaf dry matter content and leaf nitrogen and phosphorus concentrations, for 15,865 French permanent grasslands. Trait–climate relationships were tested using the following four climatic variables available across 1,833 pixels (5 km × 5 km): mean annual temperature (MAT) and precipitation (MAP), and two indices accounting for the length of the growing season. We compared these relationships at the pixel level using either using community‐level or species’ trait means. Results Our findings were as follows: (a) leaf traits related to plant nutrient economy shift consistently along a gradient of growing season length accounting for temperature and soil water limitations of plant growth (GSL tw ); (b) weighting leaf traits by species abundance in local communities is pivotal to capture leaf trait–environment relationships correctly at a biogeographical scale; and (c) the relationships between traits and GSL tw weaken for grasslands with a high nitrogen input. Main conclusions The effects of climate on plant communities are better described using composite descriptors than coarse variables such as MAT or MAP, but appear weaker for high‐nitrogen grasslands. Using information at the community level tends to strengthen trait–climate relationships. The interplay of land management, community assembly and bioclimate appears crucial to the prediction of leaf trait variations and their effects on biogeochemical cycles.

Experimentally increased nutrient availability at the permafrost thaw front selectively enhances biomass production of deep‐rooting subarctic peatland species - Frida Keuper; Ellen Dorrepaal; Peter M. van Bodegom; Richard van Logtestijn; Gemma Venhuizen; Jurgen van Hal; Rien Aerts (Global Change Biology, 2017)
Climate warming increases nitrogen (N) mineralization in superficial soil layers (the dominant rooting zone) of subarctic peatlands. Thawing and subsequent mineralization of permafrost increases plant‐available N around the thaw‐front. Because plant production in these peatlands is N‐limited, such changes may substantially affect net primary production and species composition. We aimed to identify the potential impact of increased N‐availability due to permafrost thawing on subarctic peatland plant production and species performance, relative to the impact of increased N‐availability in superficial organic layers. Therefore, we investigated whether plant roots are present at the thaw‐front (45 cm depth) and whether N‐uptake ( 15 N‐tracer) at the thaw‐front occurs during maximum thaw‐depth, coinciding with the end of the growing season. Moreover, we performed a unique 3‐year belowground fertilization experiment with fully factorial combinations of deep‐ (thaw‐front) and shallow‐fertilization (10 cm depth) and controls. We found that certain species are present with roots at the thaw‐front ( Rubus chamaemorus ) and have the capacity (R. chamaemorus, Eriophorum vaginatum ) for N‐uptake from the thaw‐front between autumn and spring when aboveground tissue is largely senescent. In response to 3‐year shallow‐belowground fertilization (S) both shallow‐ ( Empetrum hermaphroditum ) and deep‐rooting species increased aboveground biomass and N‐content, but only deep‐rooting species responded positively to enhanced nutrient supply at the thaw‐front (D). Moreover, the effects of shallow‐fertilization and thaw‐front fertilization on aboveground biomass production of the deep‐rooting species were similar in magnitude (S: 71%; D: 111% increase compared to control) and additive (S + D: 181% increase). Our results show that plant‐available N released from thawing permafrost can form a thus far overlooked additional N‐source for deep‐rooting subarctic plant species and increase their biomass production beyond the already established impact of warming‐driven enhanced shallow N‐mineralization. This may result in shifts in plant community composition and may partially counteract the increased carbon losses from thawing permafrost.

A new metric to assess the predictive accuracy of multinomial land cover models - Jacob C. Douma; William K. Cornwell; Peter M. van Bodegom (Journal of Biogeography, 2017)
Aim The earth's land cover is often represented by discrete classes, and predicting shifts between these classes is a major goal in the field. One increasingly common approach is to build models that predict land cover classes with probabilities rather than discrete outcomes. Current assessment approaches have drawbacks when applied to these types of models. In this paper we present a new metric, which assesses agreement between model predictions and observations, while correcting for chance agreement. Location Global. Methods is the product of two metrics: the first component measures the agreement in the ranks of the predicted and observed classes, the other specifies the certainty of the model in the case of discrete observations. We analysed the behaviour of and two alternative metrics: Cohen's Kappa ( ) and an extension of the area under receiver operating characteristic Curve to multiple classes ( mAUC ) when applied to multinomial predictions and discrete observations. Results Using real and synthetic datasets, we show that – in contrast to – can distinguish between models that are very far off versus slightly off. In addition, κ multinomial ranks models higher that predict observed classes with an onaverage higher probability. In contrast, mAUC gives the same score to models that are perfectly able to discriminate among classes of outcomes regardless of the certainty with which those classes are predicted. Main conclusions With we have provided a tool that directly uses the multinomial probabilities for accuracy assessment. may also be applied to cases where model predictions are evaluated against multiple sets of observations, at multiple spatial scales, or compared to reference models. As models develop we assess how well new models perform compared to the real world.

Stability in a changing world – palm community dynamics in the hyperdiverse western Amazon over 17 years - Ingrid Olivares; Jens‐Christian Svenning; Peter M. van Bodegom; Renato Valencia; Henrik Balslev (Global Change Biology, 2017)
Are the hyperdiverse local forests of the western Amazon undergoing changes linked to global and local drivers such as climate change, or successional dynamics? We analyzed local climatic records to assess potential climatic changes in Yasuní National Park, Ecuador, and compared two censuses (1995, 2012) of a palm community to assess changes in community structure and composition. Over 17 years, the structure and composition of this palm community remained remarkably stable. Soil humidity was significantly lower and canopy conditions were significantly more open in 2012 compared to 1995, but local climatic records showed that no significant changes in precipitation, temperature or river level have occurred during the last decade. Thus, we found no evidence of recent directional shifts in climate or the palm community in Yasuní. The absence of changes in local climate and plant community dynamics in Yasuní contrasts with recent findings from eastern Amazon, where environmental change is driving significant changes in ecosystem dynamics. Our findings suggest that until now, local forests in the northwest Amazon may have escaped pressure from climate change. The stability of this rich palm community embedded in the hyperdiverse Yasuní National Park underlines its uniqueness as a sanctuary for the protection of Amazonian diversity from global change impacts.

The effects of soil eutrophication propagate to higher trophic levels - Juha Pöyry; Luísa G. Carvalheiro; Risto K. Heikkinen; Ingolf Kühn; Mikko Kuussaari; Oliver Schweiger; Anu Valtonen; Peter M. van Bodegom; Markus Franzén (Global Ecology and Biogeography, 2017)
Aim Nitrogen deposition is a major global driver of change in plant communities, but its impacts on higher trophic levels are insufficiently understood. Here, we introduce and test a novel conceptual trait‐based model describing how the effects of soil eutrophication cascade to higher trophic levels across differential plant–herbivore interactions. Location Northern Europe. Methods We synthesize previous literature on the effects of nitrogen on plants and herbivorous insects as well as relevant multispecies patterns of insect communities concerning species dietary breadth, body size, dispersal propensity and voltinism in order to derive the model. We empirically evaluate the proposed, hitherto untested, four main model pathways using statistical modelling and data on 1064 northern European butterfly and moth species, their life‐history traits, phylogeny and population trends. Results We show that across all species: (1) larval dietary breadth and host plant foliar nitrogen content are positively and equally strongly related to insect body size, and that (2) multivoltinism, host plant preferences for soil nitrogen, body size and larval dietary breadth are positively related to population trends of butterflies and moths as predicted by the model. Positive relationships between plant foliar nitrogen content and body size as well as multivoltinism and population trends are the first multispecies demonstrations for these patterns. Main conclusions Soil nitrogen enrichment amplifies the diverging trends of herbivorous insects feeding on nitrophilous versus nitrophobous plants through differential plant–herbivore interactions, causing predictable changes in community composition at higher trophic levels. A positive foliar nitrogen–insect body size relationship, now empirically supported, is the integrating link within this cascade. As nitrogen deposition is a global driver, our model suggests that a major future trend may be an increased dominance of insects that are large, dispersive, multivoltine, dietary generalists or specialized on nitrophilous plant species at the expense of species preferring oligotrophic environments.

Inclusion of ecologically based trait variation in plant functional types reduces the projected land carbon sink in an earth system model - Lieneke M. Verheijen; Rien Aerts; Victor Brovkin; Jeannine Cavender‐Bares; Johannes H. C. Cornelissen; Jens Kattge; Peter M. van Bodegom (Global Change Biology, 2015)
Earth system models demonstrate large uncertainty in projected changes in terrestrial carbon budgets. The lack of inclusion of adaptive responses of vegetation communities to the environment has been suggested to hamper the ability of modeled vegetation to adequately respond to environmental change. In this study, variation in functional responses of vegetation has been added to an earth system model ( ESM ) based on ecological principles. The restriction of viable mean trait values of vegetation communities by the environment, called ‘habitat filtering’, is an important ecological assembly rule and allows for determination of global scale trait–environment relationships. These relationships were applied to model trait variation for different plant functional types ( PFT s). For three leaf traits (specific leaf area, maximum carboxylation rate at 25 °C, and maximum electron transport rate at 25 °C), relationships with multiple environmental drivers, such as precipitation, temperature, radiation, and CO 2 , were determined for the PFT s within the Max Planck Institute ESM . With these relationships, spatiotemporal variation in these formerly fixed traits in PFT s was modeled in global change projections ( IPCC RCP 8.5 scenario). Inclusion of this environment‐driven trait variation resulted in a strong reduction of the global carbon sink by at least 33% (2.1 Pg C yr −1 ) from the 2nd quarter of the 21st century onward compared to the default model with fixed traits. In addition, the mid‐ and high latitudes became a stronger carbon sink and the tropics a stronger carbon source, caused by trait‐induced differences in productivity and relative respirational costs. These results point toward a reduction of the global carbon sink when including a more realistic representation of functional vegetation responses, implying more carbon will stay airborne, which could fuel further climate change.

Global effects of soil and climate on leaf photosynthetic traits and rates - Vincent Maire; Ian J. Wright; I. Colin Prentice; Niels H. Batjes; Radika Bhaskar; Peter M. van Bodegom; Will K. Cornwell; David Ellsworth; Ülo Niinemets; Alejandro Ordonez; Peter B. Reich; Louis S. Santiago (Global Ecology and Biogeography, 2015)
Aim The influence of soil properties on photosynthetic traits in higher plants is poorly quantified in comparison with that of climate. We address this situation by quantifying the unique and joint contributions to global leaf‐trait variation from soils and climate. Location Terrestrial ecosystems world‐wide. Methods Using a trait dataset comprising 1509 species from 288 sites, with climate and soil data derived from global datasets, we quantified the effects of 20 soil and 26 climate variables on light‐saturated photosynthetic rate ( A area ), stomatal conductance ( g s ), leaf nitrogen and phosphorus ( N area and P area ) and specific leaf area ( SLA ) using mixed regression models and multivariate analyses. Results Soil variables were stronger predictors of leaf traits than climatic variables, except for SLA . On average, N area , P area and A area increased and SLA decreased with increasing soil pH and with increasing site aridity. g s declined and P area increased with soil available P ( P avail ). N area was unrelated to total soil N . Joint effects of soil and climate dominated over their unique effects on N area and P area , while unique effects of soils dominated for A area and g s . Path analysis indicated that variation in A area reflected the combined independent influences of N area and g s , the former promoted by high pH and aridity and the latter by low P avail . Main conclusions Three environmental variables were key for explaining variation in leaf traits: soil pH and P avail , and the climatic moisture index (the ratio of precipitation to potential evapotranspiration). Although the reliability of global soil datasets lags behind that of climate datasets, our results nonetheless provide compelling evidence that both can be jointly used in broad‐scale analyses, and that effects uniquely attributable to soil properties are important determinants of leaf photosynthetic traits and rates. A significant future challenge is to better disentangle the covarying physiological, ecological and evolutionary mechanisms that underpin trait–environment relationships.

Effects of Warming and Drought on the Vegetation and Plant Diversity in the Amazon Basin - Ingrid Olivares; Jens-Christian Svenning; Peter M. van Bodegom; Henrik Balslev (The Botanical Review, 2015)

Global patterns of plant root colonization intensity by mycorrhizal fungi explained by climate and soil chemistry - Nadejda A. Soudzilovskaia; Jacob C. Douma; Asem A. Akhmetzhanova; Peter M. van Bodegom; William K. Cornwell; Esther J. Moens; Kathleen K. Treseder; Mark Tibbett; Ying‐Ping Wang; Johannes H. C. Cornelissen (Global Ecology and Biogeography, 2015)
Aim Most vascular plants on E arth form mycorrhizae, a symbiotic relationship between plants and fungi. Despite the broad recognition of the importance of mycorrhizae for global carbon and nutrient cycling, we do not know how soil and climate variables relate to the intensity of colonization of plant roots by mycorrhizal fungi. Here we quantify the global patterns of these relationships. Location Global. Methods Data on plant root colonization intensities by the two dominant types of mycorrhizal fungi world‐wide, arbuscular (4887 plant species in 233 sites) and ectomycorrhizal fungi (125 plant species in 92 sites), were compiled from published studies. Data for climatic and soil factors were extracted from global datasets. For a given mycorrhizal type, we calculated at each site the mean root colonization intensity by mycorrhizal fungi across all potentially mycorrhizal plant species found at the site, and subjected these data to generalized additive model regression analysis with environmental factors as predictor variables. Results We show for the first time that at the global scale the intensity of plant root colonization by arbuscular mycorrhizal fungi strongly relates to warm‐season temperature, frost periods and soil carbon‐to‐nitrogen ratio, and is highest at sites featuring continental climates with mild summers and a high availability of soil nitrogen. In contrast, the intensity of ectomycorrhizal infection in plant roots is related to soil acidity, soil carbon‐to‐nitrogen ratio and seasonality of precipitation, and is highest at sites with acidic soils and relatively constant precipitation levels. Main conclusions We provide the first quantitative global maps of intensity of mycorrhizal colonization based on environmental drivers, and suggest that environmental changes will affect distinct types of mycorrhizae differently. Future analyses of the potential effects of environmental change on global carbon and nutrient cycling via mycorrhizal pathways will need to take into account the relationships discovered in this study.

Global drivers and patterns of microbial abundance in soil - Hector M. Serna‐Chavez; Noah Fierer; Peter M. van Bodegom (Global Ecology and Biogeography, 2013)
Aim While soil microorganisms play key roles in E arth's biogeochemical cycles, methodological constraints and sparse data have hampered our ability to describe and understand the global distribution of soil microbial biomass. Here, we present a comprehensive quantification of the environmental drivers of soil microbial biomass. Location Global. Methods We used a comprehensive global dataset of georeferenced soil microbial biomass estimates and high‐resolution climatic and soil data. Results We show that microbial biomass carbon ( C Mic ) is primarily driven by moisture availability, with this single variable accounting for 34% of the global variance. For the microbial carbon‐to‐soil organic carbon ratio ( C Mic / C Org ), soil nitrogen content was an equally important driver as moisture. In contrast, temperature was not a significant predictor of microbial biomass patterns at a global scale, while temperature likely has an indirect effect on microbial biomass by influencing rates of evapotranspiration and decomposition. As our models explain an unprecedented 50% of the global variance of C Mic and C Mic / C Org , we were able to leverage gridded environmental information to build the first spatially explicit global estimates of microbial biomass and quantified the global soil microbial carbon pool to equal 14.6 Pg C . Main Conclusions Our unbiased models allowed us to build the first global spatially explicit predictions of microbial biomass. These patterns show that soil microbial biomass is not primarily driven by temperature, but instead, biomass is more heterogeneous through the effects of moisture availability and soil nutrients. Our global estimates provide important data for integration into large‐scale carbon and nutrient models that may imply a major step forward in our ability to predict the global carbon balance, now and in a future climate.

A predictive model of community assembly that incorporates intraspecific trait variation - Daniel C. Laughlin; Chaitanya Joshi; Peter M. van Bodegom; Zachary A. Bastow; Peter Z. Fulé (Ecology Letters, 2012)
Community assembly involves two antagonistic processes that select functional traits in opposite directions. Environmental filtering tends to increase the functional similarity of species within communities leading to trait convergence, whereas competition tends to limit the functional similarity of species within communities leading to trait divergence. Here, we introduce a new hierarchical B ayesian model that incorporates intraspecific trait variation into a predictive framework to unify classic coexistence theory and evolutionary biology with recent trait‐based approaches. Model predictions exhibited a significant positive correlation ( r = 0.66) with observed relative abundances along a 10 °C gradient in mean annual temperature. The model predicted the correct dominant species in half of the plots, and accurately reproduced species' temperature optimums. The framework is generalizable to any ecosystem as it can accommodate any species pool, any set of functional traits and multiple environmental gradients, and it eliminates some of the criticisms associated with recent trait‐based community assembly models.

Highly consistent effects of plant litter identity and functional traits on decomposition across a latitudinal gradient - Marika Makkonen; Matty P. Berg; I. Tanya Handa; Stephan Hättenschwiler; Jasper van Ruijven; Peter M. van Bodegom; Rien Aerts (Ecology Letters, 2012)
Plant litter decomposition is a key process in terrestrial carbon cycling, yet the relative importance of various control factors remains ambiguous at a global scale. A full reciprocal litter transplant study with 16 litter species that varied widely in traits and originated from four forest sites covering a large latitudinal gradient (subarctic to tropics) showed a consistent interspecific ranking of decomposition rates. At a global scale, variation in decomposition was driven by a small subset of litter traits (water saturation capacity and concentrations of magnesium and condensed tannins). These consistent findings, that were largely independent of the varying local decomposer communities, suggest that decomposer communities show little specialisation and high metabolic flexibility in processing plant litter, irrespective of litter origin. Our results provide strong support for using trait‐based approaches in modelling the global decomposition component of biosphere‐atmosphere carbon fluxes.

Tundra in the Rain: Differential Vegetation Responses to Three Years of Experimentally Doubled Summer Precipitation in Siberian Shrub and Swedish Bog Tundra - Frida Keuper; Frans-Jan W. Parmentier; Daan Blok; Peter M. van Bodegom; Ellen Dorrepaal; Jurgen R. van Hal; Richard S. P. van Logtestijn; Rien Aerts (Ambio, 2012)

A frozen feast: thawing permafrost increases plant‐available nitrogen in subarctic peatlands - Frida Keuper; Peter M. van Bodegom; Ellen Dorrepaal; James T. Weedon; Jurgen van Hal; Richard S. P. van Logtestijn; Rien Aerts (Global Change Biology, 2012)
Many of the world's northern peatlands are underlain by rapidly thawing permafrost. Because plant production in these peatlands is often nitrogen ( N )‐limited, a release of N stored in permafrost may stimulate net primary production or change species composition if it is plant‐available. In this study, we aimed to quantify plant‐available N in thawing permafrost soils of subarctic peatlands. We compared plant‐available N ‐pools and ‐fluxes in near‐surface permafrost (0–10 cm below the thawfront) to those taken from a current rooting zone layer (5–15 cm depth) across five representative peatlands in subarctic Sweden. A range of complementary methods was used: extractions of inorganic and organic N, inorganic and organic N ‐release measurements at 0.5 and 11 °C (over 120 days, relevant to different thaw‐development scenarios) and a bioassay with Poa alpina test plants. All extraction methods, across all peatlands, consistently showed up to seven times more plant‐available N in near‐surface permafrost soil compared to the current rooting zone layer. These results were supported by the bioassay experiment, with an eightfold larger plant N ‐uptake from permafrost soil than from other N ‐sources such as current rooting zone soil or fresh litter substrates. Moreover, net mineralization rates were much higher in permafrost soils compared to soils from the current rooting zone layer (273 mg N m −2 and 1348 mg N m −2 per growing season for near‐surface permafrost at 0.5 °C and 11 °C respectively, compared to −30 mg N m −2 for current rooting zone soil at 11 °C). Hence, our results demonstrate that near‐surface permafrost soil of subarctic peatlands can release a biologically relevant amount of plant available nitrogen, both directly upon thawing as well as over the course of a growing season through continued microbial mineralization of organically bound N . Given the nitrogen‐limited nature of northern peatlands, this release may have impacts on both plant productivity and species composition.

Summer warming accelerates sub‐arctic peatland nitrogen cycling without changing enzyme pools or microbial community structure - James T. Weedon; George A. Kowalchuk; Rien Aerts; Jurgen van Hal; Richard van Logtestijn; Neslihan Taş; Wilfred F. M. Röling; Peter M. van Bodegom (Global Change Biology, 2012)
The balance of primary production and decomposition in northern peatlands may shift due to climate change, with potential feedbacks to atmospheric CO 2 concentrations. Nitrogen availability will modulate this shift, but little is known about the drivers of soil nitrogen dynamics in these environments. We used a long‐term (9 years) open top chamber ( OTC ) experiment in an ombrotrophic Sphagnum peat bog in sub‐arctic Sweden, to test for the interactive effects of spring warming, summer warming and winter snow addition on soil nitrogen fluxes, potential activities of nitrogen cycle enzymes, and soil microbial community composition. These simultaneous measurements allowed us to identify the level of organization at which climate change impacts are apparent, an important requirement for developing truly mechanistic understanding. Organic‐N pools and fluxes were an order of magnitude higher than inorganic‐N pools and fluxes. Summer warming approximately doubled fluxes of soil organic nitrogen and ammonia over the growing season. Such a large increase under 1 °C warming is unlikely to be due to kinetic effects, and we propose that it is linked to an observed seasonal decrease in microbial biomass, suggesting that N flux is driven by a substantial late‐season dieback of microbes. This change in N cycle dynamics was not reflected in any of the measured potential peptidase activities. Moreover, the soil microbial community structure was apparently stable across treatments, suggesting a non‐specific microbial dieback. Our results show that in these widespread peat bogs, where many plant species are capable of organic‐N uptake, organic soil N dynamics are quantitatively far more important than the commonly studied inorganic‐N dynamics. Understanding of climate change effects on organic soil N cycling in this system will be advanced by closer investigation of the seasonal dynamics of the microbial biomass and the input of substrates that maintain it.

Leaf habit and woodiness regulate different leaf economy traits at a given nutrient supply - Jenny C. Ordoñez; Peter M. van Bodegom; Jan-Philip M. Witte; Ruud P. Bartholomeus; Han F. van Dobben; Rien Aerts (Ecology, 2010)
The large variation in the relationships between environmental factors and plant traits observed in natural communities exemplifies the alternative solutions that plants have developed in response to the same environmental limitations. Qualitative attributes, such as growth form, woodiness, and leaf habit can be used to approximate these alternative solutions. Here, we quantified the extent to which these attributes affect leaf trait values at a given resource supply level, using measured plant traits from 105 different species (254 observations) distributed across 50 sites in mesic to wet plant communities in The Netherlands. For each site, soil total N, soil total P, and water supply estimates were obtained by field measurements and modeling. Effects of growth forms, woodiness, and leaf habit on relations between leaf traits (SLA, specific leaf area; LNC, leaf nitrogen concentration; and LPC, leaf phosphorus concentration) vs. nutrient and water supply were quantified using maximum‐likelihood methods and Bonferroni post hoc tests. The qualitative attributes explained 8–23% of the variance within sites in leaf traits vs. soil fertility relationships, and therefore they can potentially be used to make better predictions of global patterns of leaf traits in relation to nutrient supply. However, at a given soil fertility, the strength of the effect of each qualitative attribute was not the same for all leaf traits. These differences may imply a differential regulation of the leaf economy traits at a given nutrient supply, in which SLA and LPC seem to be regulated in accordance to changes in plant size and architecture while LNC seems to be primarily regulated at the leaf level by factors related to leaf longevity.

A global study of relationships between leaf traits, climate and soil measures of nutrient fertility - Jenny C. Ordoñez; Peter M. Van Bodegom; Jan‐Philip M. Witte; Ian J. Wright; Peter B. Reich; Rien Aerts (Global Ecology and Biogeography, 2009)
Aim This first global quantification of the relationship between leaf traits and soil nutrient fertility reflects the trade‐off between growth and nutrient conservation. The power of soils versus climate in predicting leaf trait values is assessed in bivariate and multivariate analyses and is compared with the distribution of growth forms (as a discrete classification of vegetation) across gradients of soil fertility and climate. Location All continents except for Antarctica. Methods Data on specific leaf area (SLA), leaf N concentration (LNC), leaf P concentration (LPC) and leaf N:P were collected for 474 species distributed across 99 sites (809 records), together with abiotic information from each study site. Individual and combined effects of soils and climate on leaf traits were quantified using maximum likelihood methods. Differences in occurrence of growth form across soil fertility and climate were determined by one‐way ANOVA. Results There was a consistent increase in SLA, LNC and LPC with increasing soil fertility. SLA was related to proxies of N supply, LNC to both soil total N and P and LPC was only related to proxies of P supply. Soil nutrient measures explained more variance in leaf traits among sites than climate in bivariate analysis. Multivariate analysis showed that climate interacted with soil nutrients for SLA and area‐based LNC. Mass‐based LNC and LPC were determined mostly by soil fertility, but soil P was highly correlated to precipitation. Relationships of leaf traits to soil nutrients were stronger than those of growth form versus soil nutrients. In contrast, climate determined distribution of growth form more strongly than it did leaf traits. Main conclusions We provide the first global quantification of the trade‐off between traits associated with growth and resource conservation ‘strategies’ in relation to soil fertility. Precipitation but not temperature affected this trade‐off. Continuous leaf traits might be better predictors of plant responses to nutrient supply than growth form, but growth forms reflect important aspects of plant species distribution with climate.

Plant species traits are the predominant control on litter decomposition rates within biomes worldwide - William K. Cornwell; Johannes H. C. Cornelissen; Kathryn Amatangelo; Ellen Dorrepaal; Valerie T. Eviner; Oscar Godoy; Sarah E. Hobbie; Bart Hoorens; Hiroko Kurokawa; Natalia Pérez‐Harguindeguy; Helen M. Quested; Louis S. Santiago; et al. (Ecology Letters, 2008)
Worldwide decomposition rates depend both on climate and the legacy of plant functional traits as litter quality. To quantify the degree to which functional differentiation among species affects their litter decomposition rates, we brought together leaf trait and litter mass loss data for 818 species from 66 decomposition experiments on six continents. We show that: (i) the magnitude of species‐driven differences is much larger than previously thought and greater than climate‐driven variation; (ii) the decomposability of a species’ litter is consistently correlated with that species’ ecological strategy within different ecosystems globally, representing a new connection between whole plant carbon strategy and biogeochemical cycling. This connection between plant strategies and decomposability is crucial for both understanding vegetation–soil feedbacks, and for improving forecasts of the global carbon cycle.

Effects of iron-ore mining and processing on metal bioavailability in a tropical coastal lagoon - Adriana Alves Pereira; Bert van Hattum; Abraham Brouwer; Peter Michiel van Bodegom; Carlos Eduardo Rezende; Wim Salomons (Journal of Soils and Sediments, 2008)

Global negative vegetation feedback to climate warming responses of leaf litter decomposition rates in cold biomes - Johannes H.C. Cornelissen; Peter M. Van Bodegom; Rien Aerts; Terry V. Callaghan; Richard S.P. Van Logtestijn; Juha Alatalo; F. Stuart Chapin; Renato Gerdol; Jon Gudmundsson; Dylan Gwynn‐Jones; Anne E. Hartley; David S. Hik; et al. (Ecology Letters, 2007)
Whether climate change will turn cold biomes from large long‐term carbon sinks into sources is hotly debated because of the great potential for ecosystem‐mediated feedbacks to global climate. Critical are the direction, magnitude and generality of climate responses of plant litter decomposition. Here, we present the first quantitative analysis of the major climate‐change‐related drivers of litter decomposition rates in cold northern biomes worldwide. Leaf litters collected from the predominant species in 33 global change manipulation experiments in circum‐arctic‐alpine ecosystems were incubated simultaneously in two contrasting arctic life zones. We demonstrate that longer‐term, large‐scale changes to leaf litter decomposition will be driven primarily by both direct warming effects and concomitant shifts in plant growth form composition, with a much smaller role for changes in litter quality within species. Specifically, the ongoing warming‐induced expansion of shrubs with recalcitrant leaf litter across cold biomes would constitute a negative feedback to global warming. Depending on the strength of other (previously reported) positive feedbacks of shrub expansion on soil carbon turnover, this may partly counteract direct warming enhancement of litter decomposition.

Upscaling Regional Emissions of Greenhouse Gases from Rice Cultivation: Methods and Sources of Uncertainty - Peter H. Verburg; Peter M. van Bodegom; Hugo A. C. Denier van der Gon; Aldo Bergsma; Nico van Breemen (Plant Ecology, 2006)

New Synthesis on the Diverse Effects of Biodiversity - Peter van Bodegom (Plant Ecology, 2005)

Radial oxygen loss, a plastic property of dune slack plant species - Peter M. van. Bodegom; Marleen de Kanter; Chris Bakker Rien Aerts (Plant and Soil, 2005)

Identifying key issues in environmental wetland research using scaling and uncertainty analysis - Peter van Bodegom; Chris Bakker; Hugo Denier van der Gon (Regional Environmental Change, 2004)

Effects of interpolation and data resolution on methane emission estimates from rice paddies - Peter M. Van Bodegom; Peter H. Verburg; Alfred Stein; Sri Adiningsih; Hugo A.C. Denier Van Der Gon (Environmental and Ecological Statistics, 2002)

Sulfate-containing amendments to reduce methane emissions from rice fields: mechanisms, effectiveness and costs - Hugo A. Denier van der Gon; Peter M. van Bodegom; Reiner Wassmann; Rhoda S. Lantin; Teodula M. Metra-Corton (Mitigation and Adaptation Strategies for Global Change, 2001)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)